Osmotic Behavior of Testes Interstitium Cells in Hypertonic Solutions of NaCl and PEO-400 - Chernobay, N. A.; Kovalenko, I. F.; Bozhok, G. A.; Kovalenko, S. Ye.; Pakhomov, A. V.; Rozanov, L. F. (Problems of Cryobiology and Cryomedicine, 2010)
Cell suspension obtained from the rat testes interstitium is a heterogeneous population. The minimal and maximal values of cell volume vary by two orders, and distribution of cells by size can be described as a bimodal one. The data on dehydration of testes interstitium cells in hypertonic solutions of NaCl and PEO-400 were obtained. Values of relative osmotically inactive volume in NaCl (0.3659) and PEO-400 (0.3669) solutions were determined by extrapolation of cell volume dependence on medium osmolarity to perpetual osmotic pressure.